High dynamic stiffness mechanical structures with nanostructured composite coatings deposited by high power impulse magnetron sputtering. (March 2016) - Fu, Qilin; Lorite, Gabriela Simone; Rashid, Md. Masud-Ur; Neuhaus, Raphael; Cada, Martin; Hubicka, Zdenek; Pitkänen, Olli; Selkälä, Tuula; Uusitalo, Juha; Glanz, Carsten; Kolaric, Ivica; Kordas, Krisztian; et al.
Abstract: Nanostructured Cu:CuCNx composite coatings with high static and dynamic stiffness were synthesized by means of plasma-enhanced chemical vapor deposition (PECVD) combined with high power impulse magnetron sputtering (HiPIMS). Scanning electron microscope (SEM) images and energy-dispersive X-ray spectroscopy (EDS) mapping from cross-sectioned samples reveals a multi-layered nanostructure enriched in Cu, C, N, and O in different ratios. Mechanical properties of the coatings were investigated by Vickers micro-indention and model tests. It was observed that copper inclusions as well as copper interlayers in the CNx matrix can increase mechanical damping by up to 160%. Mechanical properties such as hardness, elastic modulus and loss factor were significantly improved by increasing the discharge power of the sputtering process. Moreover the coatings loss modulus was evaluated on the basis of indentation creep measurements under room temperature. The coating with optimum properties exhibited loss modulus of 2.6 GPa. The composite with the highest damping loss modulus were applied on the clamping region of a milling machining tool to verify their effect in suppressing regenerative tool chatter. The high dynamic stiffness coatings were found to effectively improve the critical stability limit of a milling tool by at least 300%, suggesting a significant increase of the dynamic stiffness.